ASSESS THE DROUGHT TOLERANCE OF BC15 RICE VARIETIES USING INVITRO CULTURE METHOD - Thi Cuc, Bui; Huy Gioi, Dong; Thi Thu Huong, Bui (Journal of Forestry Science and Technology, 2021)
BC15 rice is a pure quality rice variety, capable of adapting to large ecological ranges, therefore chosen by farmers to cultivate on large areas. Because global warming and climate change have greatly affected the water source for irrigation, so the rice yield is significantly reduced. This study was conducted to evaluate the drought tolerance of the BC15 variety in vitro culture system to get more information about the characteristics of the BC15 variety when selecting production areas. The object of the study was to determine the most suitable artificial drought conditions for BC15 rice seedlings in vitro. The result shows that in the MS1/2 medium supplemented with PEG with osmotic potential -4 bar; or the MS1/2 supplemented with 7% Saccharose; or the MS1/2 added 3% Mannitol or MS1/2 added 4% Sorbitol, shoots of the rice can be survival. Under these artificial drought conditions caused by Saccharose, Mannitol, Sorbitol, Mannitol expressed the strongest effect on rice sprouts in vitro. Just adding 3% Mannitol to the medium, the root length and shoot height were significantly reduced compared with the control, followed by Sorbitol and finally Saccharose, significantly on the roots and shoots of the seedlings. The results of this study will support necessary information about the suitable environment to evaluate the drought tolerance of rice in vitro and the basic source for in vivo assessment.